Use of an optical rangefinder to assess the reliability of seabird flight heights from boat‐based surveyors: implications for collision risk at offshore wind farms. Issue 4 (25th October 2018) - Harwood, Andrew J. P.; Perrow, Martin R.; Berridge, Richard J.
Abstract: Visual estimates of the distribution of the flight heights of birds are often critical for collision risk assessments for wind‐energy projects. However, the reliability of such data is largely unknown. The results of trials where rangefinder height estimates were compared with those of an Unmanned Aerial Vehicle (UAV) used to mimic a flying bird at varying distances and heights from the operator suggested that the rangefinder performed well, with an overall mean deviation from the actual UAV height of −0.4 m. Accuracy and precision were influenced by an interaction between UAV height and distance to the surveyor. We also compared measurements of the flight heights of 16 species of seabirds made with an optical rangefinder to surveyor estimates made in 5‐m bands during boat‐based surveys off the east coast of Scotland UK from May to October 2017. Overall agreement between the rangefinder and surveyor estimates ( N  =   1235) was 58%, but increased to 92% when including the adjacent 5‐m bands. We found that surveyors were more likely to underestimate bird heights, potentially influencing collision‐risk assessments for wind farm projects. Use of rangefinders may be limited to days with good visibility, but their accuracy can be excellent within equipment limitations. However, suitability of rangefinders for the species or task in question should be verified before application. Further use of rangefinders is recommended for training, assessment of surveyor accuracy and consistency, calibration of visual flight height distributions, or replacement of visual observations where appropriate. Such applications could increase confidence in impact assessments and inform appropriate mitigation for wind farms.